Effect of Beta Carotene from Dehydrated Drumstick Leaf Powder on the Haematological Indices of Non Pregnant Non-Lactating Young Women Aged 18 25 Yrs Preliminary Trials - Nambiar, Dr Vanisha S (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Beta Carotene from Dehydrated Drumstick Leaf Powder on the Haematological Indices of Non Pregnant Non-Lactating Young Women Aged 18 25 Yrs Preliminary Trials